Using CR-39 Solid State Nuclear Track Detector (SSNTD) for long term monitoring of indoor and outdoor radon gas at Kuala Terengganu / Ainujariah Abdul Rahman @ Mohamad - Abdul Rahman @ Mohamad, Ainujariah (2009)
Radon is a radioactive gas that comes from the radioactive decay of uranium, which is present in small amounts almost everywhere in the Earth's crust. If radon is inhaled, it can cause harm to cells in the lungs and elsewhere. This can increased risk of cancer. Due to this, Kuala Terengganu was selected as the study area. Objectives of this study are to determine the level of radon activity concentrations in selected houses in Kuala Terengganu, Terengganu using SSNTD technique, to calibrate CR-39 SSNTD radon track detection efficiency, to compare the activity concentration with the global range value and to evaluate the possible risk that may cause by radon in the area. Technique that use for this study is SSNTD dosimeter which are the cheapest long-term monitoring device for alpha radiation from radon gas and radon daughters. Two dosimeters were located for indoor and outdoor at each selected study area. 24 houses were selected for this study. The dosimeters were collected after 105 days and brought to the laboratory. In the laboratory, SSNTD will chemically etch for 6 hours using NaOH, 6 M solutions at 70°C in the oil bath. Detectors will then washed with tap water, distilled water and drained prior to microscope inspection. From the result, the radon concentration for indoor and outdoor and annual effective dose was calculated. The radon mean concentration for indoor and outdoor is 1.18 pCi/L and a 0.28 pCi/L and the dose level ranged for our study is between 0.59 mSv/y and 1.83 mSv/y.